Theoretical Design of Dithienopicenocarbazole-Based Molecules by Molecular Engineering of Terminal Units Toward Promising Non-fullerene Acceptors - Feng, Jie; Wang, Hongshuai; Rujisamphan, Nopporn; Li, Youyong (Frontiers in Chemistry, 2020)
Dithienopicenocarbazole (DTPC) as the kernel module in A-D-A non-fullerene acceptors (NFA) has been reported for its ultra-narrow bandgap, high power conversion efficiency and extremely low energy loss. To further improve the photovoltaic performance of DTPC based acceptors, molecular engineering of end-capped groups could be an effective method according to previous research. In this article, a class of acceptors were designed via bringing terminal units with enhanced electron-withdrawing ability to the DTPC central core. Their geometrical structures, frontier molecular orbitals, absorption spectrum, intramolecular charge transfer and energy loss have been systematically investigated on the basis of density functional theory (DFT) and time-dependent density functional theory (TD-DFT) calculations. Surprisingly, NFA 4 highlights the dominance for its increased open circuit voltages while NFA 2, 7, 8 exhibit great potential for their enhanced charge transfer and lower energy loss, corresponding to higher short-circuit current density. Our results also manifest that proper modifications of the terminal acceptor with extension of π-conjugation might bring improved outcomes for overall properties. Such measure could become a feasible strategy for the synthesis of new acceptors, thereby facilitating the advancement of organic solar cells.